2021
DOI: 10.3389/fgene.2021.695130
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Signature Constructed by Immune-Related LncRNA Predicts the Immune Landscape of Colorectal Cancer

Abstract: Colorectal cancer (CRC) has the characteristics of high morbidity and mortality. LncRNA not only participates in the progression of CRC through genes and transcription levels, but also regulates the tumor microenvironment and leads to the malignant phenotype of tumors. Therefore, we identified immune-related LncRNAs for the construction of clinical prognostic model. We searched The Cancer Genome Atlas (TCGA) database for original data. Then we identified differentially expressed irlncRNA (DEirlncRNA), which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…These results suggested that the identified IRGs were important signatures of DCM. Inflammation-related genes are critical to immune stimulation and infiltration of immune cells [ 29 ]. Previous study found that expression profiles of heart tissue showed that failing and nonfailing heart expressed different genes related to immune responses, and the difference was also found between ischemic HF and nonischemic HF [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that the identified IRGs were important signatures of DCM. Inflammation-related genes are critical to immune stimulation and infiltration of immune cells [ 29 ]. Previous study found that expression profiles of heart tissue showed that failing and nonfailing heart expressed different genes related to immune responses, and the difference was also found between ischemic HF and nonischemic HF [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of eight clusters were identified, and a decreased proportion of NK cells was found in the AD group compared to the NC group (Figure 2F). IRGs are essential for immune cells to respond to immune stimulation and immune infiltration (31). An immune gene list including 212 genes was constructed by combining DEGs of each cluster and immune genes from the ImmPort database.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that multiple genes combinations is better than single gene in terms of the efficiency of a diagnostic model for tumors 16 . Recently, several studies have focused on developing a prognostic signature based on immune-related lncRNA and found that the signature could serve as a prognostic biomarker in human CRC 17 , 18 . However, most of these signatures are comprised of lncRNA pairs, which contain too much component.…”
Section: Introductionmentioning
confidence: 99%